Analysis of Consumer Behavior on Buying Decision at the Online Shop, Easy Shopping Indonesia - Dewi Indriani Jusuf (Universitas Komputer Indonesia, 2021)
Know the effect of the consumer behavior of online shop, Easy Shopping Indonesia on the consumers’ buying decision. The quantitative approach, descriptive and verified design are used. As much as 100 consumers of Essay Shopping in Bandung are selected as respondents using a purposive method. The instrument of data collection is questionnaire. The data analysis used is Structural Equation Modeling based on Partial Least Square (PLS SEM). The research results show that the consumer behavior of Easy Shopping online shop affects the consumer buying decision significantly. The biggest effect of the consumer behavior dimension on the buying decision variable is a personal factor; the second one is a psychological factor; the third one is a social factor and the fourth one is a cultural factor. The biggest effect of the consumer behavior variable is on the dimension of payment method; then the second one is distribution selection; the third one is on brand selection; the fourth one is on buying time and the last one is on product selection. Those findings are the antecedents of the online buying decision which finally affect the changes of the buying decision from the conventional buying process into the online one. Key Words : consumer behavior, cultural factors, social factors, personal factors and psychological factors, buying decision, product selection, brand selection, distribution selection, payment method and timing.